Esudio de eficiencia energética en menús completos de la Sierra Elaborados en cocinas de inducción y GLP - Alvarez Cuadros, Estefanía Divina (2015)
Throughout the years Ecuador has lived based on the 90% of the revenues from hydrocarbons, in previous years the abundance of oil led to depended only on it, at the moment our reserves are depleted and it is a problem that concerns all of us. Understanding the change of the energy matrix is the first step; the reference point is the Latin America Energy Organization that promotes the cooperation of the Latin American energy security for members. With the hydroelectric supply growth we will supply the energy consumption in our country and will have the chance to export which is also important, we will create new jobs to strengthen the hydroelectric creation. In studies 9 out of 10 Ecuadorian families use gas (GLP). The induction cooker is made of glass ceramic heating such material hits our pot with its electromagnetic field, in this process we see less loss of energy; power flow is deployed throughout the pot absorbing all the heat, so we don´t have to worry about burning. The metal contact produces an immediate cooking heat power so the food cooking is done quickly. The analysis and experimentation with the highland food menus, focusing on its temperature, cooking time between GLP versus induction cookers, help us verify which the most efficient way for cooking food is. Considering Differences between costs and subsidies.